Evolution on Ecological Carrying Capacity of Dualistic Water in County Scale Based on Matter Element Analysis Model - ZUO Taian; ZHANG Fengtai; YU Shijie; YANG Qing (Renmin Zhujiang)
The water ecological carrying capacity contains the water resource carrying capacity and the water environment carrying capacity.As one of the basic studies for integrated management of the water ecological system,this capacity connects socioeconomic development and the water ecological system.Hence its dynamic evolution reflects the dynamic equilibrium between the water ecological system and socioeconomic system.By taking the poverty-stricken Weining County in karst regions as an example,based on matter element analysis model,this paper sets up an evaluation indicator system for the ecological carrying capacity of dualistic water in county scale,and simulates the evolution of the ecological carrying capacity of dualistic water in Weining County between 2006 and 2017.The study shows that:The ecological carrying capacity of dualistic water in Weining County followed the tendency of turning for the better between 2006 and 2017.The technological advances and growing concern to the water ecological environment are two major causes of continual increases in its ecological carrying capacity of water.The ecological carrying capacity of dualistic water of Weining County between 2006 and 2017 was a tolerable level.However,the level shifted to weakly tolerable level in 2006 and 2011,meaning that the capacity was unstable and subject to extreme climatic changes.So,efforts should be made to consolidate existing achievements.Hence attention should be paid by Weining County to the dynamic changes in the reservoir filling,grade of water quality in lakes and rivers,recycle rate of industrial water,water resources per capita,water consumption per capita,and the rate of water-served population.The study will provide references for the water resource safety,ecological safety,and environmental construction in karst regions.